2020
DOI: 10.1007/s10668-020-00842-7
|View full text |Cite
|
Sign up to set email alerts
|

A trend of increasing burned areas in Iraq from 2001 to 2019

Abstract: Wildfires have an important role in the ecological process affecting ecosystems at multiple spatial scales. MCD64A1 500 m burned area product is used in this study to document trends of fire events from 2001 to 2019. The research aims to analyze the trend of burned areas in the country. Iraq is selected as study area of the research because of dramatically increasing the number of fires in the country. The study found that the lowest amount of burned areas were located in the center and southwest, while northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The July war caused major environmental damages, including direct damage to the Lebanese forests, especially in Southern Lebanon where bombing incineration caused the majority of the forest fire outbreaks as previously reported [114][115][116]. It is interesting to note that in areas of conflict, the use of intended fire as a political means to dislocate civilian populations and military forces, resulting in increased forest fires, has recently been documented (Turkish Kurdistan, Syria, Iraq) [117][118][119][120]. During the July war of 2006, the main bombing locations in Lebanon were the South (South and Nabatiyeh governorates) and the Beqaa valley (Baalbek-Hermel and Beqaa governorates); together they accounted for about 52% of the BA observed.…”
Section: Interannual Burnt Area and Trendsmentioning
confidence: 99%
“…The July war caused major environmental damages, including direct damage to the Lebanese forests, especially in Southern Lebanon where bombing incineration caused the majority of the forest fire outbreaks as previously reported [114][115][116]. It is interesting to note that in areas of conflict, the use of intended fire as a political means to dislocate civilian populations and military forces, resulting in increased forest fires, has recently been documented (Turkish Kurdistan, Syria, Iraq) [117][118][119][120]. During the July war of 2006, the main bombing locations in Lebanon were the South (South and Nabatiyeh governorates) and the Beqaa valley (Baalbek-Hermel and Beqaa governorates); together they accounted for about 52% of the BA observed.…”
Section: Interannual Burnt Area and Trendsmentioning
confidence: 99%
“…However, there was an increase in fires in both cropland areas and bare soil/sparse vegetation areas from 2017. One explanation is an increased use of fire in management of agricultural land as a method to improve soils [31]. Fires in bare soil/sparse vegetation areas are less expected, which necessitates field verification.…”
Section: Spatiotemporal Patterns Of Conflict and Fire Eventsmentioning
confidence: 99%
“…There was also an increase in fires after the failure of the peace process between the Turkish State and the Kurdistan Workers' Party in 2015 [30]. In neighbouring Iraq, Rasul et al [31] reported an increase in burned land area between 2001 and 2019, especially in the northern parts, including the Kurdistan Region of Iraq (KR-I). One of the reasons for this sharp increase in burned area was attributed to the intentional burning of cropland as well as the overall geopolitical instability in the country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the works [Rasul, et al, 2021;Ertugrul, et al, 2019;Lasko, 2019], the authors determine the dynamics of increasing the large burned areas of forest over certain periods of time using remote sensing data from the resource MCD64A1 500m. The main factors causing the increase of fires in the studied regions are analyzed.…”
Section: Introductionmentioning
confidence: 99%